Alfalfa growth and nitrogen fixation constraints in salt-affected soils are in part offset by increased nitrogen supply - Wan, Weifan; Liu, Qian; Zhang, Caihong; Li, Ke; Sun, Zhi; Li, Yuejin; Li, Haigang (Frontiers in Plant Science, 2023)
In China, alfalfa (Medicago sativa L.) is often grown on marginal land with poor soil fertility and suboptimal climate conditions. Soil salt stress is one of the most limiting factors for alfalfa yield and quality through inhibiting nitrogen (N) uptake and N fixation. To understand if N supply could improve alfalfa yield and quality through increasing N uptake in salt-affected soils, a hydroponic experiment and a soil experiment were conducted. Alfalfa growth and N fixation were evaluated in response to different salt levels and N supply levels. The results showed that salt stress not only significantly decreased alfalfa biomass by 43%-86% and N content by 58%-91% but also reduced N fixation ability and nitrogen divided from atmosphere (%Ndfa) through inhibiting nodule formation and N fixation efficiency when the salt level was above 100 mmol Na2SO4 L-1. Salt stress also decreased alfalfa crude protein by 31%-37%. However, N supply significantly improved shoot dry weight by 40%-45%, root dry weight by 23%-29% and shoot N content by 10%-28% of alfalfa grown in salt-affected soil. The N supply was also beneficial for the %Ndfa and amount of N fixed of alfalfa with salt stress., and the increase reached 47% and 60%, respectively. Nitrogen supply offset negative effect on alfalfa growth and N fixation caused by salt stress in part through improving plant N nutrition status. Our results suggest that optimal N fertilizer application is essential to alleviate loss of growth and N fixation of alfalfa in salt-affected soils.